VICTORIOUS: A Visual Analytics System for Scoping Review of Document Sets - Amir Haghighati; Amir Reza Haghverdi; Kamran Sedig (Multimodal Technologies and Interaction)
Scoping review is an iterative knowledge synthesis methodology concerned with broad questions about the nature of a research subject. The increasingly large number of published documents in scholarly domains poses challenges in conducting scoping reviews. Despite attempts to address these challenges, the specific step of sensemaking in the context of scoping reviews is seldom addressed. We address sensemaking of a curated document collection by developing a VIsual analytiCs sysTem for scOping RevIew of dOcUment Sets (VICTORIOUS). Using known methods within the machine learning community, we propose and develop six modules within VICTORIOUS: Map, Summary, Skim, SemJump, BiblioNetwork, and Compare. To demonstrate the utility of VICTORIOUS, we describe three usage scenarios. We conclude by a qualitative comparison of VICTORIOUS and other available systems. While existing systems leave their users with singular information items regarding a document set and gaining an aggregated assessment in a scoping review is often a challenge, VICTORIOUS shows promise for making sense of documents in a scoping review process.